Crisis and Legitimacy in Atlantic American Narratives of Piracy, 1678-1865 - Ganser, Alexandra (2020)
The book traces the construction and function of the pirate in transatlantic American literature from the late 17th century to the Civil War, exploring in what ways the cultural imaginary teased out the pirate's ambivalent potential as a figure of both identification and Othering, and how it has been used to negotiate ideas of legitimacy. The study recasts piracy as a discursive category moving in a continuum between the propagation of (post-)colonial adventure and accumulation on the one hand and critical commentary on exploitation and oppression on the other. Reading piracy narratives as symptomatic of various crisis scenarios in the US context, the book examines how the pirate was imbued with (de)legitimatory meaning during such periods in both elite and popular texts.